Norman-Fatimid Conflict on Sicily and its Impact on International trade in the Mediterranean - Ahmed Thehaib Hadi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
After the seized power from the majority, the Fatimids deliberately extended their political and military power to the island of Sicily, they were appointed in its rule by governors from the Caninae whose rule extended for nearly a century, and the Fatimid left a military garrison to repel the attacks of the Byzantines that aimed to seize the island, who continued in sending one campaign after another to regain control of the island, but their campaign failed. The goal of the Fatimids to remain on the island of Sicily was to secure the maritime navigation of their ships that were roaming the sea as well as to secure the flow of commercial convoys belonging to the Fatimid state and to ensure the conduct of international trade in the Mediterranean. Therefore, this island was the focus of attention of all competing powers in the Mediterranean, which led to the emergence of competition and conflict between the Byzantines and the Fatimids to control it, and then the victory of the Fatimids and their stability there, new greedy people appeared, Normands, who took advantage of the weakness of the Fatimids and their dwindling power, so they occupied the island and to get out the Fatimids from it.